2017
DOI: 10.1021/jacs.6b09863
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Driven BiOI-Based Janus Micromotor in Pure Water

Abstract: Experiment: Synthesis of BiOI microspheres:0.728 g Bi(NO 3 ) 3 •5H 2 O in 20 mL absolute ethanol in 100 mL flask and 0.249 g KI in 40 mL distilled water were prepared first. After completion of dissolution, KI solution was added drop-wise into the Bi(NO 3 ) 3 •5H 2 O solution with stir. Adjust the pH of the mixture to 7 by adding 1.5 M NH3•H2O, then, put the mixture in oil bath maintained at 80 for 3 h. The precipitates were collected by centrifugation, washed several times with distilled water and ethanol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
231
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(233 citation statements)
references
References 49 publications
2
231
0
Order By: Relevance
“…According to earlier research by Jang et al, Au/B/TiO 2 Janus micromotors showed multiwavelength responses from UV to visible light . Similar observation of micromotors propulsion by visible light was made when utilizing BiOI and Cu 2 O materials . Ren and co‐workers successfully demonstrated that motion of Au/TiO 2 Janus micromotors is strongly dependent on light intensity.…”
Section: Introductionmentioning
confidence: 65%
“…According to earlier research by Jang et al, Au/B/TiO 2 Janus micromotors showed multiwavelength responses from UV to visible light . Similar observation of micromotors propulsion by visible light was made when utilizing BiOI and Cu 2 O materials . Ren and co‐workers successfully demonstrated that motion of Au/TiO 2 Janus micromotors is strongly dependent on light intensity.…”
Section: Introductionmentioning
confidence: 65%
“…Various types of micro/nanomotors such as swimmers, biohybrid nanomotors, nanowires, and Janus micromotors have been used in environmental remediation, biomedical applications, analytical sensing, and water remediation . The Janus nanoparticles (JNPs) composed of two domains with different chemical/physical composition were initially named after the double‐faced Roman god Janus ( Figure ).…”
Section: What Is a Self‐propelled Micro/nanomotor?mentioning
confidence: 99%
“…[11,12] Near-infrared (NIR) light is an attractive stimulus with desirable light penetration and the ability to controllably irradiate the region of interest. [11,12] Near-infrared (NIR) light is an attractive stimulus with desirable light penetration and the ability to controllably irradiate the region of interest.…”
mentioning
confidence: 99%